Applicability of Self Questioning Strategy in Comprehending Narrative Text (RETAIN, 2014)
Applicability of Self Questioning Strategy in Comprehending Narrative Text Ricza Try Wicaksono English Education Faculty of Languages and Arts State University of Surabaya ricza.wicaksono@gmail.com Ahmad Munir S.Pd., M.Ed., Ph.D. English Department Faculty of Languages and Arts State University of Surabaya munstkip@yahoo.com Abstrak Penelitian ini bertujuan untuk mengujicobakan self questioning strategy dalam memahami teks naratif, khususnya untuk pelajar bahasa Inggris di Indonesia. Penelitian ini menjawab beberapa pertanyaan: (1) Dapatkah self questioning strategy digunakan untuk pelajar bahasa Inggris di Indonesia dalam memahami teks naratif? (2) Dengan mengubah pertanyaan menjadi symbol, apakah modifikasi dari self questioning strategy menambah frekuensi siswa dalam membuat pertanyaan? Penelitian ini telah membuktikan bahwa self questioning strategy dapat diterapkan pada pelajar bahasa Inggris di Indonesia. Peenelitian ini menunjukkan bahwa keuntungan – keuntungan dari self questioning strategy muncul dalam penerapannya. Simbol sebagai pengganti penulisan pertanyaan terbukti secara statistik mampu menambah frekuensi pertanyaan siswa. Cara ini mampu menghemat waktu siswa dalam penggunaan self questioning strategy. Wilcoxon Signed Rank Test menunjukkan bahwa frekuensi pertanyaan meningkat secara signifikan setelah penerapan modifikasi tersebut (p < .05). Besarnya efek dari tes tersebut adalah .71 (z = -3.201), dimana angka tersebut menunjukkan efek yang besar. Kesimpulan dalam penelitian ini adalah self questioning strategy dapat digunakan oleh pelajar bahasa Inggris di Indonesia. Modifikasi self questioning strategy dengan mengganti pertanyaan menjadi symbol terbukti efektif dalam menambah frekuensi pertanyaan siswa selama penerapan strategi tersebut berlangsung. Kata Kunci: pemahaman membaca, teks naratif, metakognitif, strategi metakognitif, self questioning strategy Abstract This study is designed to describe the applicability of self-questioning strategy in comprehending narrative text, especially for EFL students in Indonesia. This study composes some questions: (1) Can Self Questioning Strategy be applied on Indonesian students to comprehend narrative texts? And (2) Does the modification of the self questioning strategy by substitute the questions into symbols help the students generate more questions? This study has proved that the self questioning strategy is able to be applied toward the EFL students, especially in Indonesia. The study shows the benefits of the self questioning strategy which was appeared during the treatment. Symbols, as the substitution of questions writing, were proven statistically can help the students increase their question generation. Symbols helps the students save their time while using self questioning strategy by transforming the questions into symbols, so the students do not need to write down all of their questions toward the story of narrative text. This modification statistically increased the frequency of question generation. Wilcoxon Signed Rank Test shows that the data was statistically significant (p <.05). The effect size of the test is 0.71 (z = -3.201), which indicates a large effect size. The study concludes that self questioning strategy is able to be applied to Indonesian EFL students. The appropriate modification that can be used in applying self questioning strategy is question symbolizing which helps the students generate more questions. Keywords: reading comprehension, narrative text, metacognitive, metacognitive strategy, self questioning strategy INTRODUCTION There are kinds of text in English. They are descriptive, narrative, and so on. One of them is narrative. Narrative is aimed to tell stories which are about a person or a group of people overcoming problems, show how people react and experiences, explore social and cultural value, and entertain an audience (Feez & Joyce, 2000). Learn narrative is important. Garvie (1990) states the story may help to relate the item of learning, which is meaningful, interesting, and motivating. He also explains that the function of the story is as an external motivation to encourage willingness to study and the use of the story as the learning facilitator. Within those statements, students will be encouraged by narrative story because it is motivating and interesting for them. Tierney (2005) states that learning to read is not only learning to recognize words; it is also learning to make sense of texts. Less proficient learners do not recognize the purpose of reading and tend to focus on word-byword reading rather than reading for meaning (DiVesta, Hayward, & Orlando, 1979). When they fail to comprehend the test, poor readers are not as flexible as good readers in utilizing different strategies to solve the problem (Garner, 1980). According to O’Malley & Chamot’s classification of learning strategies (1990), reading strategies were divided into three categories in cognitive psychology concept as follows: (1) Cognitive strategies, (2) Metacognitive strategies, and (3) Social and affective strategies. Metacognition has an important role in reading comprehension. Good readers automatically employ metacognitive strategies to focus their attention, to derive meaning, and to make adjustments when something goes wrong (Pressley, Borkowski, and Schneider, 1987). Harris et al. (1988) also states that readers who have higher metacognitive skills are able to check for confusion or inconsistency, undertake a corrective strategy, such as rereading, relating different parts of the passage to one another, look for topic sentences or summary paragraphs, and relating the current information to their past knowledge. Teacher should teach metacognitive strategies to help students plan, control, and evaluate their learning (Thamraksa, 2005). Thamraksa also states that students with this skill will be aware of their own thinking as they perform a task and can use this awareness to control what they are doing. One of effective metacognitive strategies that teacher can use is self-questioning strategy. Self-questioning strategies is conducted when students use questions to check their own knowledge as they are learning (Darling-Hammond, Austin, Cheung, and Martin, 2003). Some researchers studied self questioning strategies. Shang and Chang-Chien (2010) conducted the research and found that self questioning is useful to enhance students’ reading comprehension because it helps students pay attention to the content of the text. It also activates their prior knowledge. King (1994) stated that when using self questioning strategy, questions designed to access learners’ prior knowledge are more effective in enhancing reading comprehension because students’ prior knowledge is to be activated. Dunlap (2007) also conducted the same research and found that the strategy was successful with the students, especially those who are struggling with second language acquisition. Those two previous studies have different subjects of study. Shang and Chang-Chien held their study with students who are freshmen majoring in English at I-Shou University, ranging from 18 to 20 years of age. However, Dunlap had different kind of participant. He included nineteen students varying in age from seven to nine years of age in a regular second grade. With these varying participants, their language use and nations, this strategy may also vary in result. Indonesian EFL students’ characteristics tend to passive, compliant, and unreflective learners (Exley; 2005). According to Pikkert and Foster (1996), they report that in Central Java Indonesian National teachers are required to present a critical evaluation of ideas for students to memorise. Their study also compares the critical thinking skills of third year Indonesian university students in Central Java with those of American secondary school and university students. They found that the Indonesian students’ scores were low. Another example is Beh (1997). Beh’s study (1997) reported that ELT in Indonesia has been unsuccessful for a number of reasons despite the introduction of a new English curriculum and the provision of in-service training for the Indonesian National teachers of English. She concludes that eighty-five per cent of the students’ spoken and written English proficiency is ‘less than good’. To increase the activeness of the students while reading, this study tried to apply the self questioning strategy. Another Shang and Chang-Chien (2010) study finding, there is a positive relationship between generating higher order questions and reading comprehension via self-questioning strategy use. It means that the more questions which are generated, the learners’ comprehension about the text is better. From those researches, this study wanted to find out whether the self questioning strategy can be applied to the EFL students of Indonesian. With the Indonesian EFL students’ characters, which are passive and unreflective, can the students apply this strategy to help them comprehending a text, especially in narrative text? This study also tested the modification of the Self-Questioning Strategy by substituting the questions into symbols whether it helps the students generate more questions or not. METHOD This study used experimental model. This study held two experiments. The experiments of this study were conducted qualitatively and quantitatively. The reason on doing experimental qualitative research was because this study tested the applicability Self Questioning Strategy on comprehending narrative texts toward EFL students in Indonesia. The experimental quantitative one was used to find out whether the modification; by transforming questions into symbols, is effective or not in increasing the students’ question frequency. This study needed a group of students and then gave the treatment to them. This study held the treatment twice. The first meeting needed to reveal the applicability of the strategy toward the students. While, the second meeting needed to apply the modification that helps the students generated more questions by transform the questions and answer into symbols. Subjects of the study were IX grader students of Al Falah Junior High School, which was consist of 20 female students (homogenous class). This class; IX-6, was chosen because the class was the superior class. The researcher gave treatment on the first meeting using conventional Self Questioning Strategy which the students need to write down all the questions that they ask include their prediction for each question. The next meeting was conducted to apply solution of a problem which came out as the result of the first meeting’s evaluation. This is what the research call as modification to the original procedure of self questioning strategy. Data were collected when the researcher was getting involved in the process of teaching and learning. There were two data collection instrument; observation and documentation. The observation result would be in the form of field notes. This study also used documentation in the form of the students’ exercise. The data in the form of field notes, and students’ work was analyzed qualitatively. In addition to qualitative analysis a quantitative analysis was conducted to measure the number of the students’ questions before and after the modification on the strategy. The benefits which were aroused became the indicator which exposed the applicability of self questioning strategy. The difference in the number of question between before and after the modification of the strategy was also calculated. APPLICABILITY OF SELF QUESTIONING STRATEGY On the first meeting, the researcher explained about Self Questioning Strategy, both its definition and implementation on narrative text. The students looked understand to the explanations. They were interested to the strategy after they became conscious to the advantages of using self questioning strategy. After giving the introduction of self questioning strategy, the researcher gave the students exercise to apply the strategy that they had learned. The exercise was simple; they had to read a narrative text and write down everything they need to know about the text. The text was titled “The Sweeper”. The researcher gave the students 10 minutes to do the exercise. While the students did their exercise, the researcher observed the students’ attitude. The researcher found that the students had no problem during the exercise. The students’ attitude showed there was no rejecting action toward the strategy. The students had done the exercise perfectly as the explanation which had been given by the researcher before. There were 85 questions generated from all students. The most frequent question which was made by the students was “What” question and “Which” question were the rarest asked questions. Almost all the student asked this question, “Who is the sweeper?”. They predicted the same thing; a wolf, some say a fox. It shows that the students used their prior knowledge on creating the prediction. The students seemed familiar with the word “sweeper” on a certain character. The students, probably, connected this “sweeper” with “Sweeper” character on kids’ show titled “Dora the Explorer”. 3 of 6 predictions from Student number 13 did not have any answer at all as the result of her reading. It indicated that student number 13 paid more attention to the text. Overall, the first meeting ran well. The strategy was applied as well as expected. The benefits of self questioning strategy were shown up. It seemed that the strategy could be applied at the moment. For the second meeting, the strategy was modified. The students were sked to do the exercise. The text of the exercise was titled “Momotaro”. The researcher explained the modification and then gave the students exercise. As like as the previous meeting, the students did not showed any rejection or obstacles to do the exercise. The researcher also counted the questions which were made by the students. The sum of questions which were generated on the second meeting was 121 questions. As like the first meeting exercise, the most frequent question which was generated was “What” and the rarest question was the same, “Which” question. Student number 1 was asking “Which one would be defeated in the fight between Momotaro and the Pirates?”. She predicted that the pirates would be defeated and she was correct. It seemed that she probably knows that the main character commonly always wins the fight. It means that student number 1 predict the answer according to her experiences. Another example is student number 14. Most of her prediction was true (4 of 6 questions). She read the text thoroughly to find out whether her predictions were true or not. In short, she was paying more attention to the text. Even the strategy was modified; the result of the application of this strategy was also the same as the first meeting. The benefits of self questioning strategy were also shown up. It indicated that the strategy could be applied on the class, considering the benefits of the self questioning strategy which were appeared on the students’ exercise. MODIFICATION OF SELF QUESTIONING STRATEGY During the implementation of self questioning strategy, the students looked struggling in writing the questions. Their number of questions they had asked was small because they short of time. It indicated that using conventional self questioning strategy is time consuming. The students’ time wasted while they write the questions. To make the questions writing shorter, the researcher planned to convert the questions into symbols. With symbols, the students would ease to note their questions without writing any questions. The researcher believes that symbols would reduce the time consumption while the students ask themselves on comprehending narrative text. This treatment purposed to reveal the effectiveness of symbols use in questioning strategy, as the modification of the strategy Ranks N Mean Rank Sum of Ranks Second Meeting Questions Frequency - First Meeting Questions Frequency Negative Ranks 2a 4.75 9.50 Positive Ranks 15b 9.57 143.50 Ties 3c Total 20 a. Second Meeting Questions Frequency < First Meeting Questions Frequency b. Second Meeting Questions Frequency > First Meeting Questions Frequency c. Second Meeting Questions Frequency = First Meeting Questions Frequency By inputting the data, the application counted it according to the formula of Wilcoxon Signed Rank Test to see whether the difference between the before and after is significant or not. The result of the data compare is on the table below. From the table above, the result shows that there were 2 students who failed increase their question frequency on the second meeting exercise. But, mostly, the students’ question were increased (Positive Ranks = 15). Still, there were students who got ties on their question frequency both on before and after the treatment (Ties = 3). Wilcoxon Signed Rank Test shows that the data was statistically significant (p <.05). The effect size of the test is 0.71 (z = -3.201), which indicating a large effect size. In conclusion, the implementation of the modification showed magnificent result. The questions which were generated statistically increased. Using Wilcoxon Signed Rank Test, the difference of comparing before and after the modification was statistically significant. The modification was proved effectively helped the students generated more questions on self questioning strategy, which would increase the students comprehension. DISCUSSION This study tries to analyze the findings during the research which was conducted in Al Falah Junior High School, especially the IX-6 grader. The first analysis is about the applicability of self questioning strategy toward Indonesian EFL students. Result of this study found that this strategy can be applied to Indonesian EFL students. It can be seen from the benefits which occurred during the treatment. Self questioning strategy let the students pay more attention to the text to improve reading comprehension (Chang, 1994). Students become active readers and independent thinkers by generating questions to understand the text. As the study found on student number 13 first exercise, she had her prediction far from the answer. However, her prediction was logic and make sense. She defined her answer by paying more attention to the story, so that she knew that her answer was wrong or maybe did not appear on the story. Even the strategy was modified; the students still focused their attention to the text. For instance, Student number 14’s exercise. She generated questions and predicted them. Most of her prediction was true (4 of 6 questions). She read the text thoroughly to find out whether her predictions were true or not. She was paying more attention to the text. In short, self questioned strategy which was applied toward Indonesian EFL students let the students pay more attention to the text. Another finding on this study supports a claim which proposed by Singer and Donlan (1982) who said that students can activate their prior knowledge through self questioning strategy which can enhance reading comprehension. Student number 5’s first exercise shows that self questioning strategy activates the student’s prior knowledge. On the second exercise, when the strategy was modified, student number 1 predicted that the pirates would be defeated and she was correct. It seemed that she probably knows that the main character commonly always wins the fight. It means that student number 1 predict the answer according to her experiences. She used her prior knowledge on writing her prediction. This finding is proving that self questioning strategy can activate the students’ prior knowledge. Those findings are the benefits of applying self questioning strategy. These findings indicate that self questioning strategy obviously can be applied toward Indonesian EFL students, since the benefits of self questioning strategy have appeared during the research. However, the strategy was time consuming even it is possible to be applied. It was the reason on doing modification of this strategy. Second analysis is about the modification of the strategy. The modification of the strategy is needed because this strategy reveals its obstacle on the first meeting of the research. The obstacle that appeared during the first meeting was that the strategy was that the strategy was time consuming. Using symbols to substitute the questions was an effective modification. Using Wilcoxon Signed Rank Test, the difference of comparing before and after the modification was statistically significant. The modification was proved effectively helped the students generated more questions on self questioning strategy, which would increase the students comprehension. It is in line with Shang and Chang-Chien (2010) study’s finding which found that there is a positive relationship between generating higher order questions and reading comprehension via self-questioning strategy use. It means that the more questions which are generated, the learners’ comprehension about the text is better. Another impact of this symbol use is that the students can be an active reader without paying attention in writing question. They can note their question even without writing any word but symbol. And the most important effect is the students can comprehend the text by asking more questions in time limitation. The symbols shorten their questions writing. All in all, self questioning strategy is another effective strategy that can be used toward the Indonesian students. It will be more effective if the strategy apply its modification in question writing, so the students will not get any hinder while comprehending a text, especially on a narrative story. CONCLUSION The students did the strategy as like as the researcher explanation without showing any rejection. The students also did not get problem while using the strategy. The benefits of self questioning appeared during the research. It indicates that self questioning strategy can be applied toward Indonesian EFL students However, this strategy was time consuming. Using symbols to substitute the quesitons helps the students increase their questions frequency. It helps the students save their time while using self questioning strategy by transforming the questions into symbols, so the students do not need to write down all of their questions toward the story of narrative text. SUGGESTIONS Since the self questioning strategy helps the students to comprehend narrative text, it is better for the students to apply the strategy to help them increase their score in reading comprehension. It is also useful for students to understand a story when they read a novel or book, so they will understand about the story for free time. Teachers better to teach their students about this strategy to help their students comprehend some text to help the students increase their score. Future researcher may conduct different modification, so the strategy will be more effective to be applied toward the Indonesian EFL students. They also may conduct the same research toward the students who has low proficiency level. REFERENCES Anderson, N. J. (2002). The Role Of Metacognition in Second/Foreign Language Teaching and Learning. ERIC Digest. Washington, DC: ERIC Clearinghouse on Languages and Linguistics Beh, Y. (1997). Current Research in Southeast Asia. RELC Journal, 28(1), 175-179. Brown, H. Douglas. (2001). Teaching by Principle. New York: Pearson Education. Cohen, D.A. (1996). Second Language Learning and Use Strategies: Clarifying The Issues. Minneapolis. Darling-Hammond, L., Austin K., Cheung M., and Martin, D. (2003) Thinking about Thinking: Metacognition. Stanford University Press Davey, B., and McBride, S. (1986a). Effects of question-generation training on reading comprehension. Journal of Educational Psychology, 78(4), 256-262. DiVesta, F. J., Hayward, K. G., & Orlando, V. P.(1979). Developmental trends in monitoring for comprehension. Child Development, 50, p. 97-105. Dunlap, J. A. (2007). The Effects of Self Questioning on Comprehension of Expository Text and Development of Content Writing with Second Grade Students. Wichita Exley, Beryl (2005) Learner Characteristics of ‘Asian’ EFL Students: Exceptions to the ‘Norm’. In Young, Janelle, Eds. Proceedings Pleasure Passion Provocation. Joint National Conference AATE & ALEA 2005, pages 1-16, Gold Coast, Australia. Flavell, J. H. (1976). Metacognitive aspects of problem solving In Resnick, L. B., The Nature of Intelligence, 12, 231-235. Lawrence Erlbaum Associates. Garner, R.(1980). Monitoring of understanding: An investigation of good and poor readers' awareness of induced miscomprehension of text. Journal of Reading Behavior, 12, 55-64. Garvie, Edie. (1990). Story as Vehicle: Teaching English to Young Children. Philadelphia: Multilingual Matters, Ltd. Grabe, W. (1991). Current developments in second language reading research. TESOL Quarterly, 25(3), 375-406. Harris, K., Graham, S., and Freeman, S. (1988). Effects of strategy training on metamemory among learning disabled students. Exceptional Children, 54, p. 332-338. Joyce, Helen de Silva and Feez, Susan. (2000). Creative writing skills. Albert Park, Victoria: Phoenix Education. King, A. (1994). Guiding knowledge construction in the classroom: Effects of teaching children how to question and how to explain. American Educational Research Journal, 31(2), 338-368. O’Malley, J. M., Chamot, A. U., Stewner-Manzanares, G., Russo, R., & Kupper, L. (1985). Learning strategy applications with students of English as a second language. TESOL Quarterly, 19, 285-296 Pressley, M., Borkowski, J.G., and Schneider, W. (1989). Good information processing: What is it and what education can do to promote it? International Journal of Educational Research, 13. 857-867. Pikkert, J. J. J. & Foster, L. (1996). Critical Thinking Skills Among Third Year Indonesian English Students. RELC Journal, 27(2), 56-64. Rose, Dale S., Parks, Michaela, Androes, Karel, Mc Mahon, & Susan, D. (2000). Improving Elementary Studnts Reading Comprehension With Drama Techniques. Journal of Educational Research Shang, Hui-Fang and Chang-Chien, I-Ju. (2010). The Effect of Self-Questioning Strategy on EFL Learners’ Reading Comprehension Development. The International Journal of Learning. I-Shou, Taiwan. Singer, H., and Donlan, D. (1982). Active comprehension: Problem-solving schema with question generation for comprehension of complex short stories. Reading Research Quarterly, 17, 166-186. Thamraksa, Chutima. (2005). Metacognition: A Key to Success for EFL Learners. Bangkok. Bangkok University. Tierney, J. E. (Ed.). (2005). Reading strategies and practices (6th ed.). Boston, MA: Pearson Education, Inc.